Penjadwalan Produksi Dengan Algoritma Heuristik Pour (Studi Kasus: Konveksi One Way – Malang) - Andri Sulaksmi; Annisa Kesy Garside; Fithriany Hadziqah (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
“One Way Convection” is a garment company which produces many kinds of t-shirt based on the customer’s order. In order to fulfill the order, the company applies role of First-Come First-Serve for scheduling the order production sequence. This role is often disadvantageous for the order with short process time because if it is dispatched after the order with long process time, then it will take longer in queue and causes the completion time of all order to be longer. This research aims to schedule t-shirt’s sequence operation in “One Way Convection” company by using Pour heuristic algorithm so that completion time becomes shorter and order fulfillment can be accomplished on-time. The steps in this methodology consist of collecting data, calculating standard time and total process time according to the order, scheduling using initial method proposed by company, scheduling using Pour heuristic algorithm, and comparing makespan of both approaches. According to the Pour Heuristic method, saving is obtained in makespan as 8.09 hours or 19.25% compared with initial method proposed by company.